Simulation of a continuous plug-flow fluidised bed dryer for rough rice (Nexo Revista Científica, 2014)
In this study, a mathematical model to simulate the drying of rough rice in a continuous plug-flow fluidised bed dryer ispresented. Equipment and material models were applied to describe the process. The equipment model was based on thedifferential equations obtained by applying mass and energy balances to each element of the dryer. Concerning the materialmodel, mass and heat transfer rates in a single isolated particle were considered. Mass and heat transfer within the particles wasdescribed by analytical solutions with constant effective transport coefficients. To simulate the dryer, the material model wasimplemented in the equipment model in order to describe the whole process. Calculation results were verified by comparisonwith experimental data from the literature. There was very good agreement between experimental data and simulation. Theeffects of gas temperature and velocity, particle diameter, dry solid flow and solid temperature on the drying process wereinvestigated. It was found that the changes in gas velocity, dry solids flow and solid temperature had essentially no effect ondrying behaviour.DOI: http://dx.doi.org/10.5377/nexo.v27i2.1947